2020
DOI: 10.31557/apjcb.2020.5.4.211-219
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Situation and Medical Management of Gynaecological and Breast Cancers from 1998 to 2018 in West Africa: A Systematic Review

Abstract: Objective: Gynaecological cancers are public health diseases and contribute to the global burden of diseases. In West Africa most have been carried out on all gynaecological and breast cases to describe the epidemiological features and management modalities.Methods: Our research covered a period from 1998 to 2018. The terms “gynaecological cancers” and “West Africa”; are used to find records in the research databases (PubMed, ScienceDirect, Scopus and Google Scholar). There are countries (Cape Verde, Guinea, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…After ligand binding, the inhibitory effect of Ptch on Smo is removed. This event causes the transformation of Smo and subsequent induction of transcription factors Gli1, Gli, Cli, and Gli3 (8,9). The activity of these transcription factors causes the transcription of hedgehog-responsive genes such as Gli, cyclin 1, and B2.…”
Section: Introductionmentioning
confidence: 99%
“…After ligand binding, the inhibitory effect of Ptch on Smo is removed. This event causes the transformation of Smo and subsequent induction of transcription factors Gli1, Gli, Cli, and Gli3 (8,9). The activity of these transcription factors causes the transcription of hedgehog-responsive genes such as Gli, cyclin 1, and B2.…”
Section: Introductionmentioning
confidence: 99%
“…They are responsible for about 850,000 deaths per year, or 30% of cancer deaths in women. The highest rates of death from gynaecological cancer were recorded in developing countries, especially in Africa [4]. Also, these cancers have a similarity from an epidemiological and diagnostic point of view, which is why it is appropriate to study them in a synoptic way for a better clinical approach.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many reports have shown that healthcare organizations worldwide suffer from poor quality, high cost, and ineffective practices due to inadequate time management, especially in oncology settings (Ramireddy et al, 2017;Vashistha et al, 2019;Zaker et al, 2019;Zaroushani et al, 2020;Zoure et al, 2020). This calls for further studies to discuss the factors that can significantly affect the adoption of lean management and improve the outcome in the healthcare setting.…”
Section: Introductionmentioning
confidence: 99%